The Oxford handbook of economic forecasting - Clements, Michael P.; Hendry, David F. (New York ; Oxford : Oxford University Press, 2011)
Greater data availability has been coupled with developments in statistical theory and economic theory to allow more elaborate and complicated models to be entertained. These include factor models, DSGE models, restricted vector autoregressions, and non-linear models.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic forecasting